Lean-TPM based production model to increase the efficiency of the finishing process in textile companies - Camones Valenzuela, Yaiza Victoria (2023)
Currently, Peruvian textile companies have played a very important role in the national economy, therefore, they are constantly seeking to implement production design strategies that allow them to obtain optimum efficiency. Accordingly, this scientific paper aims to increase efficiency in the finishing area by implementing a production model based on Lean-TPM. The results obtained can be of great value for textile industries, especially for those who wish to improve the efficiency of their operations, avoid waste and increase productivity. Therefore, the commitment to adopt new ways of working starts from the highest levels of management down to the operators, and it is important to integrate all members of the production team, because it will lead to achieve great economic benefits and be more competitive in the textile market. This article refers to the implementation of autonomous maintenance based on lean six sigma in a fabric production company where an increase from 78% to 80% in the efficiency of the finishing area was achieved.